The Effect of STEM Integrated Science Learning on Scientific Literacy and Critical Thinking Skills of Students: A Meta-Analysis - Korry Nilyani; Asrizal Asrizal; Usmeldi Usmeldi (Jurnal Penelitian Pendidikan IPA, 2023)
The development of 21st century education requires students to have 21st century skills, one of which is critical thinking skills and scientific literacy as well as technological developments that are developing rapidly so that STEM-based teaching materials are very popular for use. The purpose of this study was to determine the effect of similar research using STEM integrated science learning on students' scientific literacy abilities and critical thinking skills. The method used in this investigation is meta-analysis. The research results obtained are First, the effect of several similar studies on STEM-integrated science learning shows that STEM-integrated science learning has a very high influence on students' scientific literacy abilities and students' critical thinking skills. Second, the effect of several similar studies based on educational level shows that high school level has a higher influence on students' scientific literacy skills and students' critical thinking skills. Third, the influence of several similar studies based on the learning model used shows that the PBL model has a higher influence on students' scientific literacy skills and students' critical thinking abilities. Fourth, the effect of several similar studies based on learning subjects shows that biology subjects have a higher influence than physics and science subjects.